2016
DOI: 10.1172/jci86862
|View full text |Cite
|
Sign up to set email alerts
|

Genetic landscape of metastatic and recurrent head and neck squamous cell carcinoma

Abstract: In the process of transferring the miR-182-flox and LSL-miR-182 mice to the Jackson Laboratory, the authors realized that the description of how the LSL-miR-182 mice were generated in the manuscript contained an error. Although the miR-182-flox mice were generated by crossing the mice to a flpO deleter strain to delete the Neo cassette, as was stated in the Methods section, the R26-LSL-miR-182 mice were not crossed to a deleter strain. Instead, the R26-LSL-miR-182 mice that were utilized in this work retained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
104
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(108 citation statements)
references
References 0 publications
3
104
0
1
Order By: Relevance
“…For example, SRC has recently shown a possibility for promoting recurrence and metastasis in HNSCC. 39 In conclusion, our present study is the first one to show that SFKs inhibition is effective as an adjuvant to conventional therapy by modulating the micro and macroenvironments of HNSCC by reducing MDSCs.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…For example, SRC has recently shown a possibility for promoting recurrence and metastasis in HNSCC. 39 In conclusion, our present study is the first one to show that SFKs inhibition is effective as an adjuvant to conventional therapy by modulating the micro and macroenvironments of HNSCC by reducing MDSCs.…”
Section: Discussionmentioning
confidence: 60%
“…[39][40][41] However, the exact role of SFKs expression with immune suppressive function remains unclear. In the present study, we confirmed for the first time that SFKs inhibition by dasatinib indeed decreased tumor size and reduced MDSCs in peripheral immune organs and the tumor microenvironment of the immunocompetent HNSCC mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…Despite previous exposure to ionizing radiation and DNA-damaging cytotoxic chemotherapy, the global load of genomic alterations was high but similar between treatmentnaive tumors and recurrences, in line with the mutational burden described in whole-exome analysis of ASCC 17 and in other types of carcinoma. 18,19 Surprisingly, several individual genomic alterations were observed more frequently in the group of treatment-naive tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Next-generation sequencing has yielded insights into the genetic heterogeneity of HNSCC tumor cells in the malignant field, 26,27 tumor cells evolve over time, location (tumor microenvironment), random genetic drifting, and genetic drifting in response to chemotherapy. This constant transformation of the genetic landscape enables those cells harboring unique mutational events to drive carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%